Penegakan Sanksi bagi Pelaku Tindak Pidana Penistaan Agama oleh Konten Kreator di Indonesia - Muhammad Aldi Khoiri; Seva Maya Sari (IAIN Langsa, 2026)
This study aims to analyze the dynamics of religious blasphemy committed by content creators in Indonesia, examine the enforcement of sanctions against offenders within the national legal system, and assess the relevance of Islamic criminal law in responding to such offenses in the digital era. This research is a library study employing a qualitative approach and a normative legal method through statutory, conceptual, and case approaches. The findings indicate that religious blasphemy committed by content creators represents a transformation of religious offenses within the digital media ecosystem, characterized by the use of religious symbols, doctrines, and attributes as content designed to attract public attention within the attention economy. The enforcement of legal sanctions against offenders is supported by a robust legal framework, including Law No. 1/PNPS of 1965, Article 156a of the Indonesian Criminal Code (KUHP), Articles 300–305 of the New Criminal Code, and Article 28(2) in conjunction with Article 45A(2) of the Electronic Information and Transactions Law (ITE Law). Nevertheless, law enforcement continues to face significant challenges, including varying interpretations of the elements constituting religious blasphemy, the complexity of digital evidence, and the need to maintain a balance between the protection of religion and the right to freedom of expression.